Business management in conditions of the Russian economy digitalization - O. A. Zyablikova (Вестник университета)
Digitalization as a concept of economic activity based on digital technologies is gaining more and more popularity and is being introduced into various spheres of life. In the global aspect, digitalization covers the economies of countries of almost the whole world, which determines the triggers for the formation of their development strategies in the long term. Living in the age of digitalization, one cannot but say about it as a new phenomenon that is becoming new for the development of the state, business structures and society as a whole. The purpose of the study was to study the theoretical foundations of the digital economy and develop recommendations for the introduction of a new digital product in the activities of the organization. To achieve this goal, the method of formalization, observation and economic experiment was applied. The main results of the study were the obtained new knowledge about the digital economy, as a result of the analysis of various approaches to the definition of the digital economy from the standpoint of the sectoral approach. The place and role of Russia in the development of global digitalization processes has been determined. The opinions of scientists and business representatives regarding the opportunities and risks of digitalization for business structures, financial institutions, and the social sphere are presented. The theoretical consideration of the essence of the digital economy has received a significant practical focus. This concerns the promotion of digital products of large companies in the regions. On the example of the Penza oil and gas organization, a project for the introduction of a new digital product was considered, a hierarchical structure of work was described, and a rationale for the economic feasibility of the project was given. The further direction of the research will lie in the plane of applying flexible methodologies in the design of new projects in the field of digitalization, which are currently gaining great popularity.